Azepine-Indole Alkaloids From Psychotria nemorosa Modulate 5-HT2A Receptors and Prevent in vivo Protein Toxicity in Transgenic Caenorhabditis elegans - Kirchweger, Benjamin; Klein-Junior, Luiz C.; Pretsch, Dagmar; Chen, Ya; Cretton, Sylvian; Gasper, André L.; Heyden, Yvan Vander; Christen, Philippe; Kirchmair, Johannes; Henriques, Amélia T.; Rollinger, Judith M. (Frontiers in Neuroscience, 2022)
Nemorosine A (1) and fargesine (2), the main azepine-indole alkaloids of Psychotria nemorosa, were explored for their pharmacological profile on neurodegenerative disorders (NDs) applying a combined in silico–in vitro–in vivo approach. By using 1 and 2 as queries for similarity-based searches of the ChEMBL database, structurally related compounds were identified to modulate the 5-HT2A receptor; in vitro experiments confirmed an agonistic effect for 1 and 2 (24 and 36% at 10 μM, respectively), which might be linked to cognition-enhancing properties. This and the previously reported target profile of 1 and 2, which also includes BuChE and MAO-A inhibition, prompted the evaluation of these compounds in several Caenorhabditis elegans models linked to 5-HT modulation and proteotoxicity. On C. elegans transgenic strain CL4659, which expresses amyloid beta (Aβ) in muscle cells leading to a phenotypic paralysis, 1 and 2 reduced Aβ proteotoxicity by reducing the percentage of paralyzed worms to 51%. Treatment of the NL5901 strain, in which α-synuclein is yellow fluorescent protein (YFP)-tagged, with 1 and 2 (10 μM) significantly reduced the α-synuclein expression. Both alkaloids were further able to significantly extend the time of metallothionein induction, which is associated with reduced neurodegeneration of aged brain tissue. These results add to the multitarget profiles of 1 and 2 and corroborate their potential in the treatment of NDs.